PEMBUATAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA LEMBAGA BAHASA LIA SURABAYA - Pramijas, Danica Audi Oryza; Nurcahyawati, Vivine; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
Lembaga Bahasa LIA Surabaya is an English course that has main activity such as: class scheduling, promotion test scoring, and student attendance. At this time, class is scheduled by Head of Academic Operation Division manually. Promotion test is scored by teacher of each class one by one so there will be possibility of inaccurate score. Student attendance is recorded on paper so there will be probability of paper loss. Paper loss can cause a failure information. LB LIA requires academic information system that can cover class scheduling, promotion test scoring, and student attendance as solution for the problems. So that LB LIA can provide accurate information for students, LB LIA staffs, and parents of student.